Conceptos básicos de Tutores inteligentes (ING) - Ovares Barquero, Felipe (1993)
Intelligent tutoring Systems (ITS) are the last answer in the evolution of Computer-assisted instruction, no like a media, is an integral support, it include, media, communication, instructional subject, learner and teacher's experience. This paper deals, briefly, the general concepts of the ITS.